STUDI KOMPARASI MODEL PEMBELAJARAN SNOWBALL THROWING (ST) DAN KONVENSIONAL TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP - Nurfadilah Kris Wibowo; Bambang Priyo Darminto; Prasetyo Budi Darmono (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2020)
This study aims to determine whether the mathematics learning achievement of Grade VII students of SMP using ST learning models is better than conventional learning models. This research is a quasi-experimental study that tries to compare mathematics learning achievement between students in class VII who received treatment with ST learning models and students in class VII who received treatment with conventional learning models. The population in this study was sixth-grade students of SMP Negeri 6 Purworejo, with a total of six classes. The sampling uses the Cluster Random Sampling technique by taking two types randomly ( randomly) ) of the population to determine the sample class. The research instrument was in the form of a learning achievement test in mathematics subject matter in a flat shape. Before the research conducts, the prerequisite test was done, which includes a normality test with the Lilliefors method and a homogeneity test with the Bartlett method, and a balance test with the T-test. After the achievement test data obtain, then the prerequisite tests are carried out, including the normality test with the Lilliefors method and the homogeneity test with the Bartlett method. In the final stage, a hypothesis test performed using a t-test with a significance level of ( ) 0, 05. Based on the results of data analysis with the hypothesis test shows that mathematics learning achievement of VII graders using ST learning models is better when compared to conventional learning models.